LEADERSHIP STYLE, ORGANIZATIONAL CULTURE, AND HUMAN CAPITAL INVESTMENT: THEIR IMPACT ON BUSINESS SUSTAINABILITY AND EMPLOYEE PERFORMANCE IN INDONESIAN STARTUPS - Suhara, Ade (Gapenas Publisher, 2025)
This study investigates the impact of leadership style, organizational culture, and human capital investment on business sustainability and employee performance in Indonesian startups. A quantitative approach was employed using 175 valid responses collected through a structured questionnaire with a five-point Likert scale. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS 3). The results demonstrate that leadership style, organizational culture, and human capital investment significantly influence business sustainability and employee performance, both directly and indirectly. Business sustainability was found to play a mediating role, strengthening the relationship between organizational practices and performance outcomes. These findings highlight the critical importance of visionary leadership, adaptive culture, and continuous human capital investment in enhancing startup resilience and competitiveness. The study contributes to the literature by extending the Resource-Based View (RBV) and sustainability frameworks in the context of emerging economies, while offering practical implications for startup leaders to integrate sustainable practices into their organizational strategies.